2012
DOI: 10.4236/psych.2012.311140
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Rejection Has an Indirect Effect on Young Women’s Drinking to Cope

Abstract: While it has been documented that perceived parental rejection is associated with the use of alcohol, it has not been documented if perceived parental rejection is associated with drinking motives, or self-perceived reasons for drinking alcohol. Therefore, the purpose of the present study was to determine if, among young women specifically, perceived parental rejection has an indirect effect, via negative self-esteem, on the drinking motives of coping, enhancement, and sociability. Ninety-five female young adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Contrary to expectations, neither parent‐child relationships nor emotional well‐being contributed to either motive for drinking. This is inconsistent with previous research, which has demonstrated that negative emotional well‐being is related to greater endorsement of coping motives in adolescents (Willem et al, 2012) and poorer parent‐adolescent relationships is indirectly related to greater endorsement of coping motives in young women (Rundell et al, 2012). Perhaps rather than predicting the development of drinking motives, these variables moderate the effects of drinking motives on subsequent alcohol‐related outcomes.…”
Section: Drinking Motivescontrasting
confidence: 94%
See 1 more Smart Citation
“…Contrary to expectations, neither parent‐child relationships nor emotional well‐being contributed to either motive for drinking. This is inconsistent with previous research, which has demonstrated that negative emotional well‐being is related to greater endorsement of coping motives in adolescents (Willem et al, 2012) and poorer parent‐adolescent relationships is indirectly related to greater endorsement of coping motives in young women (Rundell et al, 2012). Perhaps rather than predicting the development of drinking motives, these variables moderate the effects of drinking motives on subsequent alcohol‐related outcomes.…”
Section: Drinking Motivescontrasting
confidence: 94%
“…Research indicates that supportive parent–child relationships are related to less frequent drunkenness in adolescence (Wolff & Crockett, 2011; Čablová, Pazderková, & Miovský, 2014) and fewer alcohol‐related problems in early adulthood (Serido, Lawry, Li, Conger, & Russell, 2014). Notably, Rundell, Brown, and Cook (2012) found that parental rejection was indirectly associated with higher endorsement of drinking to cope motives in young women, supporting a link between parent–child relationships and drinking motives.…”
Section: Drinking Motivesmentioning
confidence: 96%
“…Youth who do not report such involvement are more prone to associate with deviant peers (Chassin et al 1993), engage in risky behaviors (Hemovich et al 2011), and use illicit substances at higher rates (Crano et al 2008; Dever et al 2012). In addition, parental involvement has been linked to variations in self-esteem: higher involvement relates to more self-esteem and thus lower incidence of risk behaviors (Parker and Benson 2005); conversely, lower levels have indirect negative effects on adolescents’ decisions to consume alcohol through increased self-derogation (Rundell et al 2012). …”
Section: Problem Behavior Theorymentioning
confidence: 99%